Identification and Evaluation of Antibacterial Compounds from the Vibrio sp. associated with the Ascidian Pycnoclavella diminuta - Dermawan, Abdurraafi’ Maududi; Julianti, Elin; Putra, Masteria Yunovilsa (UI Scholars Hub, 2019)
This study aims to obtain secondary metabolites that have antibacterial activity from bacteria endophytic of ascidian Pycnoclavella diminuta collected from the coast of Bitung, North Sulawesi, Indonesia. The research was started with screening antibacterial activity of six bacteria isolated from P. diminuta. The active bacteria were selected for identification using standard biological molecular method and further fermentation to produce secondary metabolites. The isolation of secondary metabolites was conducted by various chromatography method and then selected fraction was based on the antibacterial activity from bioautography results. The result showed that the active isolate by coding M2.Tnk.Bt 5.10-3.2 was identified as Vibrio sp. The potential active fraction was further sub-fractionated by HPLC semi-preparative and each of these sub-fractions was tested against Staphylococcus aureus, Bacillus cereus, Enterococcus faecalis, Eschericia coli, and Vibrio cholerae. The test results showed that all 17 sub-fractions were active against Gram-positive bacteria S. aureus and B. cereus, and only one sub-fraction (SFr 2) showed antibacterial activity against E. faecalis. Whereas in Gram-negative bacteria, 2 sub-fractions (SFr 12 and SFr 13) showed antibacterial activity against E. coli and 12 sub-fractions active against V. cholerae. GC-MS analysis of the SFr 2 sub-fraction showed the presence of fifteen phytochemical constituents with a major compound Pyrrolo [1,2-a] pyrazine-1,4-dione, hexahydro-3- (2 methylpropyl).